2021
DOI: 10.3390/brainsci11040508
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Open-Label Placebos on State Anxiety and Glucocorticoid Stress Responses

Abstract: Stress belongs to the most frequent negative feelings people are confronted with in daily life. Strategies against acute stress include, e.g., relaxation techniques or medications, but it is also known that placebos can successfully reduce negative emotional stress. While it is widely held that placebos require deception to provoke a response, recent studies demonstrate intriguing evidence that placebos may work even without concealment (e.g., against anxiety or pain). Most of these studies are based on self-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 55 publications
2
11
0
Order By: Relevance
“…We report that an OLP treatment reduced self-reported measures of emotional distress in healthy subjects, which is in line with previous literature on effects of OLPs on emotional distress or anxiety (e.g., [7,12,13]). Moreover, we also replicated this beneficial effect of OLPs on emotional distress in an fMRI environment, allowing us to understand the neural mechanisms underlying the OLP effect.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We report that an OLP treatment reduced self-reported measures of emotional distress in healthy subjects, which is in line with previous literature on effects of OLPs on emotional distress or anxiety (e.g., [7,12,13]). Moreover, we also replicated this beneficial effect of OLPs on emotional distress in an fMRI environment, allowing us to understand the neural mechanisms underlying the OLP effect.…”
Section: Discussionsupporting
confidence: 91%
“…For example, Mathur et al examined whether OLPs affect wound healing and found no results [10]. Leibowitz et al investigated physiological allergic responses and found no direct main effects, but an interaction with the belief in placebos ( [11] similar [12]). Guevarra et al employed an electroencephalographic (EEG) approach to examine emotional distress in healthy subjects and reported OLP effects on EEG markers for both, neutral and negative stimuli [13].…”
Section: Introductionmentioning
confidence: 99%
“…Empirically, our findings show that deceptive and open placebos were equally efficacious in reducing the selfconscious emotion of guilt. These findings are in line with a growing number of reports that have found OLPs to have significant effects on emotions, including anxiety 36,71 , depression 37,38 , sadness 16,28 , general emotional wellbeing 72,73 , and emotional distress 74 . Furthermore, our results are also in line with studies reporting that DPs and OLPs have equal effects in healthy subjects 21,22,57 , which highlights the potential of OLPs as a means of ethically harnessing placebo effects in these conditions.…”
Section: Discussionsupporting
confidence: 89%
“…Five studies investigated the effect of an OLP on pain 16 , 22 , 25 , 28 , 29 . Three studies examined the influence of OLPs on well-being 19 , 23 , three on stress 18 , 31 , and two on arousal 32 , 34 . OLPs have also been studied in relation to wound healing 26 , sadness 24 , itchiness 27 , test anxiety 30 , cycling performance 21 , physiological recovery 33 , and muscle strength and fatigue 20 .…”
Section: Resultsmentioning
confidence: 99%
“…OLPs have also been studied in relation to wound healing 26 , sadness 24 , itchiness 27 , test anxiety 30 , cycling performance 21 , physiological recovery 33 , and muscle strength and fatigue 20 . A wide range of placebos was used in the studies, including a nasal spray 18 , 24 , 29 , pills 23 , 26 , 30 , 31 , creams 16 , 25 , 28 , capsules 20 , 21 , bottled water 19 , decaffeinated coffee 32 , 34 , verbal suggestions 27 , acupuncture 33 , and intravenous injection 22 . The degree of instructional suggestiveness was similarly distributed across studies, with five studies receiving a rating of 0 regarding the degree of instructional suggestiveness 24 , 29 , 32 34 , six studies receiving a rating of 1 18 20 , 27 , four studies receiving a rating of 2 21 , 25 , 26 , 28 , and five studies receiving a rating of 3 16 , 22 , 23 , 30 , 31 .…”
Section: Resultsmentioning
confidence: 99%